PENGARUH KOMPETENSI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI APARATUR SIPIL NEGARA (ASN) PADA DINAS TENAGA KERJA KOTA DEPOK - Syaiful Anwar; Yasnimar Ilyas; Muhlis Muhlis; Hamzah Fachrurozi (Institut Teknologi dan Bisnis Dewantara, 2023)
The purpose of this study was to find out how much influence Competence and Leadership Style have on the Performance of State Civil Servants (ASN) at the Depok City Manpower Office. Data analysis techniques used multiple linear regression analysis tests and hypothesis testing. The results showed that: (1) There is a significant influence of competence on employee performance with a t count of 3.879 > t table of 2.021 with a significance value of 0.000 <0.05. (2) There is a significant influence of leadership on employee performance with a t count of 4.051 > t table of 2.021 with a significance value of 0.000 <0.05. (3) The results of the simultaneous hypothesis test show that the calculated F value is 28.067 > F table 2.839 with a significance of 0.000 <0.05, this proves that together the competency and leadership variables have a significant effect on employee performance. (4) The test results for the coefficient of determination obtained an adjusted R² value of 0.581. This proves that 58.1% of employee performance is influenced by competence and leadership, while the remaining 41.9% of employee performance is influenced by other variables which were not examined in this study.